2018
DOI: 10.7717/peerj.5616
|View full text |Cite
|
Sign up to set email alerts
|

Distraction of cyclists: how does it influence their risky behaviors and traffic crashes?

Abstract: BackgroundUndisputedly, traffic crashes constitute a public health concern whose impact and importance have been increasing during the past few decades. Specifically, road safety data have systematically shown how cyclists are highly vulnerable to suffering traffic crashes and severe injuries derived from them. Furthermore, although the empirical evidence is still very limited in this regard, in addition to other human factors involved in cycling crashes, distractions while cycling appear to be a major contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 60 publications
(78 reference statements)
4
27
0
Order By: Relevance
“…During their trips, both cyclists and other road users are commonly exposed to a great amount of information, traditionally translated into the demands of different factors such as traffic signaling, billboards, noise and the risky behaviors of other road users [29,34,54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During their trips, both cyclists and other road users are commonly exposed to a great amount of information, traditionally translated into the demands of different factors such as traffic signaling, billboards, noise and the risky behaviors of other road users [29,34,54].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is worth discussing the role of distractions in traffic crashes involving bicycle riders. In a recent empirical study performed on cyclists from 20 different countries, Useche, Alonso, Montoro & Esteban [34] found that the mechanism through which distractions represent a threat for cycling safety is their relationship with cycling errors as a statistical mediator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, ‘Distraction’ was unexpectedly the only infraction inversely associated with death and statistically significant, but this category included a wide range of sources of distraction, such as involuntary risky behaviours and intentionally committed behaviours (eg, use of technological devices). Although other authors have found distraction to be associated with a higher risk of crash,22 to our knowledge, the association between distractions and the severity of the crash has not been previously assessed. A possible explanation for this inverse association with death could be the lower speed (an unobserved variable) while cycling distracted 41.…”
Section: Discussionmentioning
confidence: 70%
“…The second part consisted of shared bicycle travel-related information, such as typical purpose of shared bicycle travel, number of shared bicycle riding hours a week, and riding time for average shared bicycle rides. The third and final part of the survey asked about frequency of engaging in eight unsafe shared bicycle riding behaviors: (1) not wearing helmets [4], [5], [6], [7], (2) running red lights [8], (3) cycling against the traffic flow [9], (4) riding in a motor vehicle lane where bicycles are prohibited, (5) riding in a pedestrian lane where bicycles are prohibited, (6) carrying passengers on a shared bicycle with only one seat [10], (7) using a cell phone while riding a shared bicycle, and (8) eating while riding a shared bicycle [11], [12]. The eight risky behaviors were developed through a series of steps involving a thorough review of existing research literature and media reports, multi-round group discussions among the research team, and pilot testing.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%